Mechanisms, molecular and sero-epidemiology of antimicrobial resistance in bacterial respiratory pathogens isolated from Japanese children - Sunakawa, Keisuke (BioMed Central, 2007)
BACKGROUND: The clinical management of community-acquired respiratory tract infections (RTIs) is complicated by the increasing worldwide prevalence of antibacterial resistance, in particular, β-lactam and macrolide resistance, among the most common causative bacterial pathogens. This study aimed to determine the mechanisms and molecular- and sero-epidemiology of antibacterial resistance among the key paediatric respiratory pathogens in Japan. METHODS: Isolates were collected at 18 centres in Japan during 2002 and 2003 from children with RTIs as part of the PROTEKT surveillance programme. A proportion of Haemophilus influenzae isolates was subjected to sequencing analysis of the ftsI gene; phylogenetic relatedness was assessed using multilocus sequence typing. Streptococcus pneumoniae isolates were screened for macrolide-resistance genotype by polymerase chain reaction and serotyped using the capsular swelling method. Susceptibility of isolates to selected antibacterials was performed using CLSI methodology. RESULTS AND DISCUSSION: Of the 557 H. influenzae isolates collected, 30 (5.4%) were β-lactamase-positive [BL+], 115 (20.6%) were BL-nonproducing ampicillin-resistant (BLNAR; MIC ≥ 4 mg/L) and 79 (14.2%) were BL-nonproducing ampicillin-intermediate (BLNAI; MIC 2 mg/L). Dabernat Group III penicillin binding protein 3 (PBP3) amino acid substitutions in the ftsI gene were closely correlated with BLNAR status but phylogenetic analysis indicated marked clonal diversity. PBP mutations were also found among BL+ and BL-nonproducing ampicillin-sensitive isolates. Of the antibacterials tested, azithromycin and telithromycin were the most active against H. influenzae (100% and 99.3% susceptibility, respectively). A large proportion (75.2%) of the 468 S. pneumoniae isolates exhibited macrolide resistance (erythromycin MIC ≥ 1 mg/L); erm(B) was the most common macrolide resistance genotype (58.8%), followed by mef(A) (37.2%). The most common pneumococcal serotypes were 6B (19.7%), 19F (13.7%), 23F (13.5%) and 6A (12.8%). Telithromycin and amoxicillin-clavulanate were the most active antibacterials against S. pneumoniae (99.8% and 99.6% susceptibility, respectively). CONCLUSION: Approximately one-third of H. influenzae isolates from paediatric patients in Japan are BLNAI/BLNAR, mainly as a result of clonally diverse PBP3 mutations. Together with the continued high prevalence of pneumococcal macrolide resistance, these results may have implications for the clinical management of paediatric RTIs in Japan.